Improving the Quality of Faith in Human Resources Through Integrated Training - Mustamin, Mustamin (SEIKO : Journal of Management & Business, 2023)
Various strategies for developing human resources, especially students, that can be carried out by teachers to improve the quality of processes and learning outcomes in the classroom. One of them is the act of integrating the values of faith and piety in the learning process. Therefore, this article is the result of classroom action research which aims to describe the human resource development of students from the aspects; (1) the level of students' learning motivation students before integrating the values of faith and devotion in the learning process, (2) the level of students' learning motivation in students after integrating the values of faith and piety in the learning process, (3 ) there are differences in the level of learning motivation of students before and after integrating the values of faith and devotion in the learning process. The results of this study are obtained that there is a change in the behavior of students in participating in learning. These changes in behavior are based on observations of researchers and teachers during the learning process, where changes in student behavior have a tendency to increase in all indicators. This is indicated by the percentage of achievement from 68% to 77%, while the level of motivation has changed from 66% to 79%. Therefore, researchers assume that changes in behavior and motivation by students are caused by the treatment given. Kata Kunci: integrated learning, increased faith